Congenital Measles in a Premature 25-week Gestation Infant. Issue 8 (23rd June 2021) - Hanft, Erin; Brachio, Sandhya; Messina, Maria; Zachariah, Philip; Sutton, Desmond; Goffman, Dena; Pike, Janett; Covington, Lesley; Graham, Krishika A.; Crouch, Bindy; Adams, Eleanor; Ahmad, Nina; et al.
Abstract : We describe a premature infant with congenital measles. Laboratory testing confirmed measles in the mother (polymerase chain reaction- and IgM-positive) and congenital measles in the infant (polymerase chain reaction-positive, culture-positive and IgM-positive). The infant never developed a rash, pneumonia, or neurologic complications. This case supports using compatible laboratory findings to diagnose congenital measles in infants without clinical manifestations of measles.